Beauty And The Beast From A Cognitive Linguistic Perspective: Animal Metaphors For Women In Serbian And Romanian - KILYENI ANNAMARIA (Gender Studies, 2014)
Under the theoretical wing of Conceptual Metaphor Theory, we present a contrastive cognitive and linguistic analysis of the women are animals metaphor as used in Romanian and Serbian. Our main aim is to establish whether the names of the same animals are used in the two languages to conceptualise women and their various characteristics (particularly physical appearance and character traits), or alternatively, whether the two languages exhibit any linguistic or conceptual differences in this regard.